COVID-19 PANDEMIC VS. PUBLIC TRANSPORT ATTRACTIVENESS - LITERATURE RESEARCH AND SELECTED SOLUTIONS AND RECOMMENDATIONS (Perner's Contacts, 2021)
This paper deals with a literature search of authors dealing with public transport and the decline in passenger demand during the ongoing COVID-19 pandemic. The recommendations and conclusions of this article serve as a partial basis for the elaboration of dissertations, the topic, content and goal of which will respect and respond to this ongoing situation concerning the pandemic.